TANGGUNG JAWAB PENGURUS TERHADAP PROGRAM KEGIATAN DALAM HIMPUNAN MAHASISWA PROGRAM STUDI PENDIDIKAN MASYARAKAT, FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN, UNIVERSITAS RIAU - Ihsanul Haqqi; Said Suhil Achmad; Daeng Ayub (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This study examines the Responsibilities of Management towards Program Activities in the Student Association of the Community Education Study Program, Faculty of Teacher Training and Education, University of Riau. Responsibility is seen as awareness of one's behavior and actions. This is in accordance with the opinion of Joko (2011: 154) which means that responsibility is awareness of intentional or unintentional behavior and actions. The purpose of this study was to determine the level of responsibility of the management for the program of activities in the student association of the Community Education study program, Faculty of Teacher Training and Education, Riau University. This research is a descriptive study with a quantitative approach, the instrument used for data collection is a questionnaire with a population of 34 people. This study uses a saturated sampling technique. Research Data and Instruments 1. Primary Data, 2. Secondary Data, 3. Instruments. The instrument in this research is in the form of a questionnaire or questionnaire based on the lattice. Research instruments with research variables are the responsibility of the management towards the program with indicators consisting of; (1) ability, (2) awareness, (3) attitude and (4) behavior. To be clearer using sub-indicators, a) test measuring instruments, b) test validity, c) test reliability. The data analysis techniques used in this study were descriptive statistical analysis and inferential statistical analysis, which were carried out using Microsoft Excel and SPSS version 23 for Windows. Descriptive statistical analysis was conducted to describe the respondent's profile data in the form of the Mean and Standard Deviation of the questionnaire results, based on the respondent's demographics, variables, indicators and questionnaire items, then inferential statistical analysis was used to test the hypotheses that had been formulated previously.The conclusions from the results of this study are as follows; It is known that the responsibility of the management for the program of activities is quite high. This can be seen from 4 indicators, the highest indicator is attitude. Thus the responsibility of the management towards the program of activities in the student association is quite high, it can be seen from the attitude of the management.Key Words: Management Responsibilities, Program Activities, Student Association